Unraveling personality in mood disorders: the role of big five personality traits in Han Chinese women with bipolar and unipolar depression - Yuchen Lin; Jieying Gan; Zonglin He; Ting Yang; Xiuhua Wu; Qi Zhu; Zhaoyu Gan (Frontiers in Psychiatry)
BackgroundPersonality traits are closely related to psychiatric disorders, but their role in distinguishing major depressive disorder (DD) from bipolar disorder (BD) remains unclear. The Big Five Inventory (BFI) is widely used to assess personality, yet findings on trait differences between BD and MDD and their relationship with clinical features are inconsistent. This study examines how personality traits vary across mood disorders and their associations with clinical features.ObjectiveThis study aims to investigate how Big Five personality traits differ between major depressive disorder (MDD) and bipolar disorder (BD) and to explore their associations with clinical characteristics, including illness severity, hospitalization history, and comorbidities, in a sample of Han Chinese women.MethodsA cross-sectional analysis was conducted on BD, MDD, and healthy participants. Personality traits were assessed using the Chinese version of BFI-44, and clinical data including depression severity (HAMD scores), hospitalization history, and comorbidities were collected. Multiple regression, multivariate analysis of variance (MANOVA) and structural equational model (SEM) were used to examine group differences and associations between personality and clinical variables.ResultsBD and MDD patients exhibited higher neuroticism than healthy controls (p<0.001). BD patients had lower agreeableness than MDD (β=-0.14, p=0.04), while extraversion did not significantly differentiate the disorders. BD-I patients had higher openness than BD-II (M=2.78, p=0.02) and higher conscientiousness than BD-NOS (M=3.51, p=0.03). Higher openness correlated with physical comorbidities (β = 0.19, p = 0.01), and neuroticism was strongly linked to depression severity (β = 0.26, p < 0.001).ConclusionsNeuroticism is a key marker of psychiatric illness, while agreeableness distinguishes BD from MDD. The associations between personality, illness severity, and treatment engagement highlight their potential clinical relevance and need for further study.